Taking humor seriously in contemporary food research. (27th May 2019) - Jackson, Peter; Meah, Angela
ABSTRACT: This paper highlights the social significance of humor in everyday interactions with food within families and related household contexts. The paper approaches humor in relational terms, emphasizing its role in negotiating the way power is exercised within the moralized context of "feeding the family." Having reviewed previous work on the social significance of humor, the paper provides some examples of food-related humor from recent research with British food consumers, illustrating what such occasions reveal about participants' relations with each other, with us as researchers, and with the food they consume. Specifically, participants were found to use apologetic and self-deprecating humor to negotiate the moral ambiguities of food and to cover potentially embarrassing situations; to express familiarity and disgust regarding their current consumption practices; and to excuse potentially shameful behavior or guilty pleasures. The paper argues that an understanding of the "background disposition" through which consumers make sense of their multiple encounters with food is critical to the analysis of food-related humor and that ethnographic methods are particularly adept at revealing the social context in which humor occurs.